Sustainable Shallot (Allium cepa L) Farming Development Model in Payung Village, Karo Regency - Ruth Riah Ate Tarigan; Tharmizi Hakim; Gery Tarido Sembiring (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study aims to analyze the development model of sustainable shallot farming in Payung Village, Payung District, Karo Regency. The research method uses qualitative and quantitative approaches with data collection techniques through in-depth interviews, field observations, and surveys. The research sample includes shallot farmers, agricultural extension workers, and related stakeholders. The results of the study show that the development of sustainable shallot farming requires a comprehensive strategy that pays attention to ecological, economic, and social aspects. The key factors identified include: Implementation of environmentally friendly cultivation practices, Efficient management of land resources, Use of superior seeds and appropriate agricultural technology, Access to adequate capital and markets, and Institutional empowerment of farmers. Internal factors that become strengths are natural resource parameters, farmer experience parameters, shallot production parameters and land area parameters. The dominant force influencing the development of shallot farming in the research area is natural resources. Internal factors that are weaknesses are farmer capital parameters, onion seed parameters, input use parameters and farmer partnership parameters. The most dominant weakness is farmer capital. External factors of opportunities are market demand parameters, farming profit parameters, agroindustry infrastructure and supporting facilities parameters and support parameters for groups and extension workers. The most dominant opportunity is market demand. Recommended development models include: ongoing technical assistance, farmer capacity building, product diversification, and strengthening partnerships between farmers, the government, and the private sector. This research is expected to contribute to increasing productivity, sustainability, and welfare of shallot farmers in the region